2017
DOI: 10.1371/journal.pone.0189830
|View full text |Cite
|
Sign up to set email alerts
|

Age-related nomograms for antral follicle count and anti-Mullerian hormone for subfertile Chinese women in Singapore

Abstract: BackgroundAntral follicle count (AFC) and anti-Mullerian hormone (AMH) are known as the most reliable markers of a woman’s ovarian reserve and are related to age. There is currently no specific local age-related centile charts for AFC and AMH. Therefore, we aim to examine the relationship between AFC and AMH with age and construct age-related nomograms among a subfertile Asian population.MethodsThis is a study involving Chinese women who had their AFC and AMH measured as part of their subfertility screening fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…As AFC and AMH levels decline over age, age-related nomograms can be used as a reference to tailor the ovarian stimulation regime in IVF. (11) The ovarian reserve markers in our study had broadly similar measurements across the different ethnic groups in our study. However, we acknowledge that the small number (n = 62) of patients from minority ethnic groups limited our ability to draw conclusions about interethnic group differences.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As AFC and AMH levels decline over age, age-related nomograms can be used as a reference to tailor the ovarian stimulation regime in IVF. (11) The ovarian reserve markers in our study had broadly similar measurements across the different ethnic groups in our study. However, we acknowledge that the small number (n = 62) of patients from minority ethnic groups limited our ability to draw conclusions about interethnic group differences.…”
Section: Discussionsupporting
confidence: 61%
“…(8,9) There are limited studies on ovarian reserve markers in response to controlled ovarian stimulation in multi-ethnic Southeast Asian women in Singapore. (10,11) This may be important, as it has been shown that AMH level may be influenced by ethnicity. For example, AMH levels can be 25% lower in Afro-American and Hispanic women compared to Caucasians, with genetic polymorphism being implicated.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies indicate that at any given age, there is a considerable variation in serum AMH levels ( 14 , 17 , 18 ). Thus, similar to what has been observed for antral follicle count (AFC), large interindividual variation exists for AMH levels ( 19 , 20 ). Ethnicity may contribute to this variation and should be taken into account when interpreting AMH values.…”
Section: Serum Amh Levels In the General Populationsupporting
confidence: 66%
“…Because she had undergone right salpingo-oophorectomy and left ovarian tumorectomy previously, her AMH level was 1.53 ng/mL. It was reported that the mean AMH level was 4.18 ng/mL in 1009 Chinese women aged 26 -44 years [14]. Thus, our patient's AMH level was relatively low.…”
Section: Discussionmentioning
confidence: 64%